Patterns of metabolic adaptation for preterm and term infants in the first neonatal week. Issue 4 (April 1992) - Hawdon, J M; Ward Platt, M P; Aynsley-Green, A
Abstract : There have been few comprehensive accounts of the relationships between glucose and other metabolic fuels during the first postnatal week, especially in the context of modern feeding practises. A cross sectional study was performed of 156 term infants and 62 preterm infants to establish the normal ranges and interrelationships of blood glucose and intermediary metabolites in the first postnatal week, and to compare these with those of 52 older children. Blood glucose concentrations varied more for preterm than for term infants (1.5-12.2 mmol/l v 1.5-6.2 mmol/l), and preterm infants had low ketone body concentrations, even at low blood glucose concentrations. Breast feeding of term infants and enteral feeding of preterm infants appeared to enhance ketogenic ability. Term infants had lower prefeed blood glucose concentrations than children but, like children, appeared to be capable of producing ketone bodies. This study demonstrates that neonatal blood glucose concentrations should be considered in the context of availability of other metabolic fuels, and that the preterm infant has a limited ability to mobilise alternative fuels.